INDONESIAN JUNIOR HIGH SCHOOL STUDENTS' INTEREST IN READING BOOKS - Yeni Fitriyani (Faculty of Cultures and Languages UIN Raden Mas Said, 2022)
This research aimed to investigate Indonesian junior high school students' interest in reading books in the digital era, the factors that influence their interest, and the teacher's efforts to increase their interest in reading books in the digital era. The participants of this study were the students and the English teacher of VIII A and VIII B classes of MTs Muhammadiyah 2 Kalijambe Sragen in the academic year 2021/2022. The researcher used a mixed-method research design using quantitative and qualitative data and analysis. The data were collected through interviews and observations. The results revealed that the students' interest in reading books in the digital era was 31%. Several factors influenced the students' interest in reading books, both internal and external. The students' willingness and laziness/boredom were revealed as the internal factors, while the external factors were gadgets, the types of text or reading materials, and free time. The teacher's efforts to increase the students' interest in reading were by providing interesting books, having reading activities together, creating a comfortable place and atmosphere, and analyzing texts together. This study implies the prominent role of a teacher in increasing students' interest in reading books.